Factors Affecting Human Papillomavirus Vaccination in Men: Systematic Review - Hyunjeong Shin; Songi Jeon; Inhae Cho; HyunJi Park (JMIR Publications, 2022)
BackgroundDespite the high risks associated with human papillomavirus (HPV), the HPV vaccination rate of men is far lower than women. Most previous review studies have focused on female vaccination and related affecting factors. However, previous studies have reported that the factors affecting HPV vaccination differ by gender. ObjectiveThe aim of this review was to identify the factors affecting HPV vaccine initiation in men through a systematic review approach. MethodsA literature review was conducted across 3 central electronic databases for relevant articles. A total of 30 articles published between 2013 and 2019 met the inclusion criteria and were reviewed in this study. ResultsIn total, 50 factors affecting HPV vaccination in men were identified, including 13 sociodemographic factors and social structure factors, 12 belief-related variables, 4 family factors, 4 community factors, 14 variables related to needs, and 3 environmental factors. ConclusionsTo increase HPV vaccination rates in men, strategies targeting young males and their families should consider frequent visits to or contact with health care providers so that health care professionals can provide recommendations for HPV vaccination.